Novel optimal recursive filter for state and fault estimation of linear stochastic systems with unknown disturbances - Khémiri, Karim; Ben Hmida, Fayçal; Ragot, José; Gossa, Moncef (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies recursive optimal filtering as well as robust fault and state estimation for linear stochastic systems with unknown disturbances. It proposes a new recursive optimal filter structure with transformation of the original system. This transformation is based on the singular value decomposition of the direct feedthrough matrix distribution of the fault which is assumed to be of arbitrary rank.
Keywords: Kalman filtering; minimum-variance estimation; state estimation; fault estimation; unknown disturbances; linear discrete-time systems